2021
DOI: 10.1099/acmi.0.000293
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic detection, antimicrobial susceptibility and virulence profile of staphylococci in the pig production setting, Makurdi, Nigeria

Abstract: Livestock, particularly pigs, have increasingly been recognized as important reservoirs for zoonotic transmission of pathogenic bacteria, including staphylococci. Livestock production systems in developing countries of sub-Saharan Africa, including Nigeria, are characterized by high misuse/abuse of antimicrobials and a close association between humans and these animals, which promotes the emergence and transmission of resistant and potentially virulent bacteria. In the present study, we investigated the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Antimicrobial susceptibility testing (AST) revealed that the S. aureus isolates, both MRSA and MSSA, demonstrated high levels of resistance (100%) to β-lactam antibiotics including penicillin, ampicillin, and amoxicillin-clavulanic acid. This resistance pattern is similar to the findings reported by Mamfe et al [17], who observed a 100% resistance to βlactam antibiotics by Staphylococci isolates in Makurdi, Nigeria, and this may be attributed to the possibility that the isolates may have acquired the ability to produce β-lactamase due to prolonged antibiotic misuse, thereby, neutralising the antibiotic effects of β-lactams.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Antimicrobial susceptibility testing (AST) revealed that the S. aureus isolates, both MRSA and MSSA, demonstrated high levels of resistance (100%) to β-lactam antibiotics including penicillin, ampicillin, and amoxicillin-clavulanic acid. This resistance pattern is similar to the findings reported by Mamfe et al [17], who observed a 100% resistance to βlactam antibiotics by Staphylococci isolates in Makurdi, Nigeria, and this may be attributed to the possibility that the isolates may have acquired the ability to produce β-lactamase due to prolonged antibiotic misuse, thereby, neutralising the antibiotic effects of β-lactams.…”
Section: Discussionsupporting
confidence: 90%
“…A prevalence of 31.2% (29/93) was obtained which was significantly higher than the 6.5% reported in a previous cross-sectional study conducted by Odetokun et al [16], who used phenotypic and molecular techniques to identify S. aureus from the nasal swabs of slaughtered pigs, goats, cattle, and abattoir workers in Ibadan and Ilorin. Other recent studies that have reported a level of occurrence of Staphylococcus aureus similar to our findings include Mamfe et al [17], who reported a prevalence of 19.1% from the nasal swabs of pigs in Makurdi and Sineke et al [18], reported a prevalence of 29.1% from a combination of samples, particularly pig faecal samples, farm slurry samples, and human nasal swabs in pig production settings in South Africa. The relatively high prevalence observed in the various recent studies points towards the fact that pigs are important carriers of the pathogen and may contribute to the propagation of S. aureus to humans.…”
Section: Discussionsupporting
confidence: 89%
“…The minimum number of samples to be collected (sample size) was estimated to be 163 using a 95% con dence level, an expected methicillin resistance prevalence of 12% (19) and desired precision of 5% (23) in order to describe the prevalence of methicillin-resistant Staphylococcus spp. Differences in the prevalence of SOSA species and antibiotic resistance rates between the two farms were calculated using Fisher exact and Chi squared tests where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA is often analyzed from food and livestock samples (Aires-de-Sousa et al, 2017; Sergelidis and Angelidis, 2017). Besides their resistance to almost all beta-lactam antibiotics, resistance to vancomycin and linezolid, which are considered last resort antibiotics and therefore critical, has become a significant concern for human and animal health for reducing treatment choices of severe infections caused by MRSA (Onaran et al, 2019;Mamfe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%